The History of Don Quixote, Volume 1, Part 08 - Cervantes Saavedra, Miguel de, 1547-1616; Doré, Gustave, 1832-1883; Ormsby, John, 1829-1895 (Salt Lake City, UT : Project Gutenberg, 2004)
"The History of Don Quixote, Volume 1, Part 08" by Miguel de Cervantes Saavedra is part of a novel originally published in 1605. The story follows Alonso Quijano, a man so consumed by chivalric romances that he loses his sanity and becomes the knight-errant Don Quixote. Accompanied by his earthy squire Sancho Panza, he embarks on delusional adventures, mistaking windmills for giants and inns for castles, unable to distinguish fantasy from reality in his quest to revive chivalry. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Don_Quixote
Illustrated.
Release date is 2004-06-01
Produced by David Widger
Keywords: Spain -- Social life and customs -- 16th century -- Fiction; Knights and knighthood -- Spain -- Fiction; Picaresque literature; Romances